2012
DOI: 10.1186/1752-153x-6-78
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity comparison of extracts from various parts of common and tartary buckwheats: evaluation of the antioxidant- and angiotensin-converting enzyme inhibitory activities

Abstract: BackgroundBuckwheat flour and buckwheat sprouts possess antioxidant properties, and previous studies have reported on buckwheat flour displaying an inhibitory activity for angiotensin-I converting enzyme (ACE). Information is lacking on the bioactivity of other parts of the buckwheat, such as the seed hulls and plant stalks. This study investigates the ACE inhibitory activity and antioxidant activity of various parts of 2 types of buckwheat, namely, common buckwheat (Fagopyrum esculentum Moench) and tartary bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Common buckwheat (Fagopyrum esculentum) and tartary buckwheat (Fagopyrum tartaricum) are regarded as traditional foodstuffs available worldwide (Tsai and others ). Because little is known of the ACE inhibitory activity of the other parts of the buckwheat plant, Tsai and others () studied the bioactivities of different parts and varieties of buckwheat. It was discovered that 50% ethanolic extracts of buckwheat hulls showed the greatest ACE inhibitory activity (IC 50 = 30 μg·cm −3 ).…”
Section: Plantsmentioning
confidence: 99%
“…Common buckwheat (Fagopyrum esculentum) and tartary buckwheat (Fagopyrum tartaricum) are regarded as traditional foodstuffs available worldwide (Tsai and others ). Because little is known of the ACE inhibitory activity of the other parts of the buckwheat plant, Tsai and others () studied the bioactivities of different parts and varieties of buckwheat. It was discovered that 50% ethanolic extracts of buckwheat hulls showed the greatest ACE inhibitory activity (IC 50 = 30 μg·cm −3 ).…”
Section: Plantsmentioning
confidence: 99%
“…IC 50ACE for hypertonic and isotonic salts was not so different, however hypertonic amino acids-enriched salt showed a statistically significant higher value: 11 lg/ mL against 7.4 mg/mL for the isotonic one. Results can be considered interesting if it is observed that IC 50ACE for commonly used anti-hypertensive drugs is 2-4.5 ng/mL for Captopril and 190 ng/mL for Lisinopril (Sigma-Aldrich), while anti-hypertensive peptides (from milk) generally show IC 50ACE in the range 90-200 lg/mL, and quercetin, rutin, and vegetable like celery show IC 50ACE of 39, 86 and 666 lg/mL, respectively [42][43][44]. Sodium chloride showed no inhibition on the ACE (Table 2).…”
Section: Anti-hypertensive Activitymentioning
confidence: 99%
“…An example of an ACE inhibitory sequence derived from common buckwheat is a tripeptide GPP (Gly-Pro_Pro) with an IC 50 = 6.25 μg protein/mL [ 5 ]. However, buckwheat is a rich source of phenolic compounds and only a few reports were on extracts from various parts of common and tartary buckwheat [ 19 ]. Buckwheat flour also displays inhibitory activity for the angiotensin-I converting enzyme [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Buckwheat flour also displays inhibitory activity for the angiotensin-I converting enzyme [ 20 , 21 , 22 ]. Tsai et al [ 19 ] found high ACE inhibitory activities of 50% ethanolic extracts from buckwheat hulls and groat. Moreover, deionized water extracts of groat also showed the inhibition of ACE which probably resulted from the presence of water-soluble peptides or phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%